A Data-driven approach to renewable energy source planning at regional level. Issue 11 (2nd December 2021) - Surmonte, Francesco; Perna, Umberto; Scala, Antonio; Rubino, Alessandro; Facchini, Angelo
ABSTRACT: A correlation analysis based on Markowitz Portfolio Theory and data from meteorological station are used to develop a decision-making tool for the optimal spatial installation of renewable energy sources from Wind turbines and PV panels. A case study involving power generation plants and weather stations in the region of Tuscany in Italy is developed. The results show that temporal correlations of solar and wind generation profiles are characterized by correlation and anticorrelation. This feature is used for supporting decision-making on investments in renewable energy at the territorial level.